Critical assessment of the management practices of Dr. Yusuf Dadoo Hospital - Sofohlo, Patrick Mbeko (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPA (Public Management and Planning))--University of Stellenbosch, 2010.